Public and performance in the Greek theatre - Arnott, Peter D. (Routledge, 1991)
Professor Arnott discusses the practical staging of Greek plays, and relates theatre practice to literary structure by demonstrating, for example, how the buildings themselves imposed particular constraints on actors and writers alike.